2020
DOI: 10.1155/2020/2654208
|View full text |Cite
|
Sign up to set email alerts
|

How Much Do We Know about the Biopsychosocial Predictors of Glycaemic Control? Age and Clinical Factors Predict Glycaemic Control, but Psychological Factors Do Not

Abstract: Objective. Diabetes mellitus is one of the most common noncommunicable diseases in Malaysia. It is associated with significant complications and a high cost of treatment, especially when glycaemic control is poor. Despite its negative impact on health, data is still lacking on the possible biopsychosocial predictors of poor glycaemic control among the diabetic population. This study is aimed at determining the prevalence of poor glycaemic control as well as its association with biopsychosocial factors such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 41 publications
1
15
0
2
Order By: Relevance
“…A study done in Malaysia showed that a longer duration of DM was a predictor of poor glycemic control. 25 The finding is similar to the finding of this study in which inadequate blood sugar control was significantly associated with a longer duration of the disease. The negative relationship between longer duration of DM and blood glucose control may related to the resistance of insulin production over time which resulted from β-cell dysfunction.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A study done in Malaysia showed that a longer duration of DM was a predictor of poor glycemic control. 25 The finding is similar to the finding of this study in which inadequate blood sugar control was significantly associated with a longer duration of the disease. The negative relationship between longer duration of DM and blood glucose control may related to the resistance of insulin production over time which resulted from β-cell dysfunction.…”
Section: Discussionsupporting
confidence: 89%
“…The finding of this study showed that the prevalence of poor blood glucose control was 80.3% which was higher than a study done in Malaysia where the prevalence of poor glycemic control was 69%. 25 The discrepancy in those studies may also be explained by the fact that this study used Fasting Blood Sugar (FBS) for measuring glycemic control, whereas in other studies, they used hemoglobin A1c (HbA1c) test for measuring glycemic control. Furthermore, it may be due to differences in study participants’ social and economic class which may in turn influence access to health care, drug, and balanced nutrition.…”
Section: Discussionmentioning
confidence: 91%
“…The average annual expense of treatment and management of patients with diabetes in Bangladesh was estimated to be US$314, with the average direct cost being US$283 and the indirect being US$315 [ 7 ]. Apart from the economic standpoints, the mere existence of diabetes also takes a psychological toll on the individual diagnosed, due to this disease’s chronic manifestations and auxiliary clinical complications [ 8 10 ]. The continuous restrictions to food and medications often render a patient’s mind to think these efforts are futile, resulting in poor glycemic control, more complications and poor quality of life [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…, 젊은 연령 [10,11], 낮은 교육수준 [12], 흡연 [13], 긴 당뇨병 유병기간 [7], 경구용혈당강하제와 인슐린 복합치료인 경우 [9], 혈중지질이 높은 경우 [2], 비만 [7,11], 감소된 신체활동 [8]…”
unclassified